La calidad y benchmarking, como herramienta de crecimiento, caso de un spa en Morelia - Tinoco Mejía, Gricelda (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
This study is oriented towards the application of quality and benchmarking tools in a Spa organization, with the solid purpose of promoting its growth. The research was carried out through direct observation, opinion polls, telephone calls and consultation of web pages; thus, allowing the collection of relevant information on the needs and preferences of customers, for later comparison with our competition in the local market. In a context where continuous improvement, quality management and benchmarking are crucial to maintain competitiveness and service excellence, this study reveals that our organization is a company with many strengths, such as offering services and products with a lot of quality and variety, however, areas of opportunity are also identified, in which actions and services will be implemented to further increase their performance. This summary highlights the interaction of these approaches in the spa industry and highlights their influence on the ability to adapt to changing client demands; In addition to emphasizing that quality is not only an objective in itself, but a fundamental basis for the successful achievement of the organization's objectives. For all these reasons, the study shows that the adoption of continuous improvement practices, quality management and benchmarking drive the evolution of the organization in question. Although there are outstanding services and diversity of offers, there is room to optimize procedures and expand the range offered. The intersection of these approaches in the spa environment underscores their influence on customer satisfaction and adaptability. In the first instance, therefore, quality is established as an essential foundation in the search for business success in this industry.

El presente estudio se orienta hacia la aplicación de herramientas de calidad y benchmarking en una organización Spa, con el sólido propósito de fomentar el crecimiento de esta. La investigación se llevó a cabo mediante observación directa, encuestas de opinión, llamadas telefónicas y consulta de páginas web; permitiendo así recopilar información relevante sobre las necesidades y preferencias de los clientes, para comparación posterior con nuestra competencia en el mercado local. En un contexto donde la mejora continua, la gestión de calidad y el benchmarking son cruciales para mantener la competitividad y la excelencia en el servicio, este estudio revela que nuestra organización es una empresa con muchas fortalezas, como la oferta de servicios y productos con mucha calidad y variedad; no obstante, también se identifican áreas de oportunidad, en las que se implementarán acciones y servicios para elevar aún más su desempeño. Este resumen destaca la interacción de estos enfoques en la industria del spa y resalta su influencia en la capacidad de adaptación a las demandas cambiantes de los clientes; además de enfatizar, que la calidad no es solo un objetivo en sí mismo, sino una base fundamental para el logro exitoso de los objetivos de la organización. Por todo ello, el estudio demuestra que la adopción de prácticas de mejora continua, gestión de calidad y benchmarking, impulsan la evolución de la organización en cuestión. Aunque se cuenta con servicios destacados, y diversidad de ofertas, existe margen para optimizar procedimientos y ampliar la gama ofertada. La intersección de estos enfoques en el ámbito del spa, subraya su influencia en la satisfacción del cliente y la capacidad de adaptación. En primera instancia, por tanto, la calidad se establece como un cimiento esencial en la búsqueda del éxito empresarial en esta industria.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2023-0903; Mejora continua; Clientes; Satisfacción; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16657